2011
DOI: 10.1158/0008-5472.can-10-2386
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Genetic Demonstration of a Role for Activator E2Fs in Myc-Induced Tumors

Abstract: Advances in genomic signatures have begun to dissect breast cancer heterogeneity and application of these signatures will allow the prediction of which pathways are important in tumor development. Here we used genomic signatures to predict involvement of specific E2F transcription factors in Myc-induced tumors. We genetically tested this prediction by interbreeding Myc transgenics with mice lacking various activator E2F alleles. Tumor latency decreased in the E2F1 mutant background and significantly increased … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 32 publications
3
53
1
Order By: Relevance
“…While exploring the role of E2F1 in tumor development, we found that loss of E2F1 enhanced ductal transformation and accelerated tumor onset. In a previous study of Myc-mediated tumorigenesis, we noted a similar acceleration of tumor onset with loss of E2F1 (19). In agreement with the role of E2F1 in Myc-induced apoptosis (43), we noted that loss of E2F1 reduced the level of apoptosis and caused Myc tumors to grow more quickly.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While exploring the role of E2F1 in tumor development, we found that loss of E2F1 enhanced ductal transformation and accelerated tumor onset. In a previous study of Myc-mediated tumorigenesis, we noted a similar acceleration of tumor onset with loss of E2F1 (19). In agreement with the role of E2F1 in Myc-induced apoptosis (43), we noted that loss of E2F1 reduced the level of apoptosis and caused Myc tumors to grow more quickly.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, in prostate cancer, patients with detectable nuclear staining for E2F3 had worse prognoses than patients for whom E2F3 was undetectable (27). Furthermore, we demonstrated recently that E2Fs also play a role in relapse-free survival time in human breast cancer (19). Together, these prior studies and was imaged using a goat anti-rabbit secondary antibody (product no.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…E2F2 has a strong ability to promote cell cycle progression (27), and aberrant expression of E2F2 can lead to abnormal cellular proliferation. Upregulation of E2F2 has been reported in prostate (28), breast cancer (29) and astrocytoma (30). Our data on OS cells are consistent with those from previous studies reporting that the upregulation of E2F2 may contribute to cell malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, breast cancer cells with molecular alterations affecting the Rb pathway or E2F overexpression display altered chemotherapeutic responses (32)(33)(34)(35)(36), including resistance to the Cdk4/Cdk6 inhibitor PD-0332991 (37,38). Mouse models demonstrated the requirement for E2Fs in mammary carcinogenesis, since ablation of E2F1 and E2F3 suppressed Her2/Neu and Myc-induced mammary tumorigenesis (26,39,40). Thus, studying E2F functions may provide clues not only to understanding how mammary tumors initiate and progress but also to how breast cancer cells fail to respond to common therapies.…”
mentioning
confidence: 99%